P474 Efficacy and safety of GCAP therapy for UC with PSC. (15th January 2020) - Ito, A; Murasugi, S; Omori, T; Yonezawa, M; Tokushige, K
Abstract: Background: Primary sclerosing cholangitis (PSC) is a disease with poor prognosis that progresses to cirrhosis due to chronic inflammation of unknown cause. PSC is a progressive disease, and it is essential to control infection such as recurrent cholangitis, so treatment for UC with PSC is desirable because it does not suppress the immune mechanism. Among certain UC treatments, granulocyte adsorption therapy (GCAP) has been reported as a highly safe treatment method with almost no drug load. To clarify the efficacy and safety of GCAP for ulcerative colon associated with PSC. We examined for the purpose. Methods: We examined patients with PCAP with UC ( n = 35) who were in our hospital from April 2000 to July 2019 ( n = 9) who were treated with GCAP. Items to be considered Background factors, the presence/absence of steroid combination (0.5 mg/kg or more), 2. Remission induction rate (remission rate after 5 GCAP treatments: remission is defined as CAI is 4 or less), 3. Safety (adverse events caused by GCAP, GCAP We compared the liver function before and after the treatment. Results: 1. Gender (M/F: 4/5), age (age) 45.2 ± 24.3, Affected range (all colitis/right-sided/rectitis 9/0/0), clinical score before GCAP treatment (Lichtiger score: CAI) 7.4 ± 2.0, Alb (g/dl) 3.0 ± 0.9, T-bil (mg/dl) 0.7 ± 0.3, ALP (U/l) 653 ± 390, γ-GTP (U/l) 63.4 ± 27.7, endoscopic score (Mayo 1.5 ± 0.7, UCEIS 2.8 ± 1.5), steroid combination rate was 22.2% 2. Remission induction rate was 77.7% 3. Safety harmful to GCAP the events were only fever ( n = 1) and poor return ( n = 1). Hepatic function did not deteriorate before and after GCAP. Conclusion: GCAP was performed in mild to moderate cases, with a high remission rate of 77.7% and fewer steroid combinations. For UC with PSC, GCAP is an effective and safe treatment for induction of remission, suggesting that it may be an option in the future.